Agile Scrum Analysis Of Stakeholder Management Effectiveness In The Batam Real Estate Industry (Case Study: Pt Crisanta Jaya Abadi) - Fernando Jose; Zulkarnain Zulkarnain; Syaeful Anas Aklani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The real estate industry in Batam City faces dynamic market conditions and high stakeholder complexity, requiring the adoption of flexible and adaptive project management approaches. Agile Scrum has emerged as an alternative method; however, empirical studies examining its implementation in stakeholder management within the real estate sector remain limited. This study aims to analyze the implementation of Agile Scrum and its impact on the effectiveness of stakeholder management in real estate projects at PT Crisanta Jaya Abadi. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with eight informants consisting of company management and project team members directly involved in project execution. The collected data were analyzed using thematic analysis to identify key patterns and themes based on stakeholder perceptions. The results indicate that the implementation of Agile Scrum enhances flexibility in responding to dynamic stakeholder requirements, improves project transparency and communication effectiveness, and supports faster and more accurate cross-functional decision-making. Furthermore, both internal and external stakeholder involvement becomes more active through continuous feedback mechanisms throughout the project lifecycle. Nevertheless, the success of Agile Scrum implementation is strongly influenced by human resource readiness and consistency in applying Agile principles. This study is expected to provide practical insights for real estate companies and contribute to academic literature on the application of Agile Scrum in non-information technology sectors.